Synergy between early-incorporation immunotherapy and extracranial radiotherapy in metastatic non-small cell lung cancer - Chodavadia, Parth A. (Transl Lung Cancer Res, 2021)
BACKGROUND: Combining radiotherapy (RT) and immunotherapy (IT) may enhance outcomes for metastatic non-small cell lung cancer (mNSCLC). However, data on the immunomodulatory effects of extracranial RT remains limited. This retrospective database analysis examined real-world practice patterns, predictors of survival, and comparative effectiveness of extracranial radioimmunotherapy (RT + IT) versus early-incorporation immunotherapy (eIT) in patients with mNSCLC. METHODS: Patients diagnosed with mNSCLC between 2004–2016 treated with eIT or RT + IT were identified in the National Cancer Database. Practice patterns were assessed using Cochrane-Armitrage trend test. Cox proportional hazards and Kaplan-Meier method were used to analyze overall survival (OS). Propensity score matching was performed to account for baseline imbalances. Biologically effective doses (BED) were stratified based on the median (39 Gy(10)). Stereotactic body radiotherapy (SBRT) was defined as above median BED in ≤5 fractions. RESULTS: eIT utilization increased from 0.3% in 2010 to 13.2% in 2016 (P<0.0001). Rates of RT + eIT increased from 38.8% in 2010 to 49.1% in 2016 among those who received eIT (P<0.0001). Compared to eIT alone, RT + eIT demonstrated worse median OS (11.2 vs. 13.2 months) while SBRT + eIT demonstrated improved median OS (25 vs. 13.2 months) (P<0.0001). There were no significant differences in OS based on sequencing of eIT relative to RT (log-rank P=0.4415) or irradiated site (log-rank P=0.1606). On multivariate analysis, factors associated with improved OS included chemotherapy (HR 0.86, P=0.0058), treatment at academic facilities (HR 0.83, P<0.0001), and SBRT (HR 0.60, P=0.0009); after propensity-score multivariate analysis, SBRT alone showed improved OS (HR 0.28, P<0.0001). CONCLUSIONS: Utilization of RT + eIT in mNSCLC is increasing. SBRT + eIT was associated with improved OS on propensity-score matched analysis. There were no significant differences in OS based on RT + eIT sequencing or site irradiated. Whether these observations reflect patient selection or possible immunomodulatory benefits of RT is unclear and warrants further study.